Faktor- Faktor Yang Mempengaruhi Perilaku Seks Bebas Pada Remaja SMK Di Kota Bitung - Rahim, Hindun; Ardiningtyas, Lisa; Saputri, Erni Ernawati Citra Dwi (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
This study aims to identify the factors influencing free sexual behavior among vocational high school students in Bitung City. The objectives include understanding the impact of parental roles, social media exposure, and knowledge of sexual health on adolescent behavior. A quantitative approach was employed, utilizing surveys distributed to 200 students. The results indicate a significant correlation between parental guidance and reduced instances of free sexual behavior. Additionally, increased knowledge of reproductive health was associated with more responsible sexual behavior. The study concludes that enhancing parental involvement and sexual education can mitigate risky behaviors among adolescents. Recommendations include implementing comprehensive sexual education programs in schools.